Clinical characteristics and etiology of bacterial meningitis in Chinese children >28 days of age, January 2014–December 2016: A multicenter retrospective study. (September 2018) - Li, Chi; Feng, Wen-ya; Lin, Ai-wei; Zheng, Guo; Wang, Yan-chun; Han, Yan-jun; Zhong, Jian-min; Bi, Jing; Luo, Qiong; Zhao, Fang-chao; Jin, Ping; Guo, Ling-yun; et al.
Abstract: Objective: To explore the clinical characteristics and etiology of bacterial meningitis (BM) in Chinese children. Method: BM cases in children 28 days to 18 years old were collected from January 2014–December 2016 and screened according to World Health Organization standards. Clinical features, pathogens, and resistance patterns were analyzed. Results: Overall, 837 cases were classified into five age groups: 28 days–2 months (17.0%), 3–11 months (27.8%), 12–35 months (24.0%), 3–6 years (13.9%), and >6 years (17.3%). Major pathogens were Streptococcus pneumoniae ( S. pneumoniae, n = 136, 46.9%), group B Streptococcus (GBS, n = 29, 10.0%), and Escherichia coli ( E. coli, n = 23, 7.9%). In infants <3 months old, GBS (46.5%) and E. coli (23.3%) were most common; in children >3 months old, S. pneumoniae (54.7%), which had a penicillin non-susceptibility rate of 55.4% (36/65), was most frequent. The resistance rates of S. pneumoniae and E. coli to cefotaxime and ceftriaxone were 14.0%/40.0% and 11.3%/68.4%, respectively. All GBS isolates were sensitive to penicillin. Conclusions: The occurrence of BM peaked in the first year of life, while S. pneumoniae was the predominant pathogen in children >3 months of old. The antibiotic resistance of S. pneumoniae was a concern.